2015
DOI: 10.1016/j.humov.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of “Relationship between BMI, waist circumference, physical activity and probable developmental coordination disorder over time”

Abstract: pDCD is associated with higher body mass and waist circumference, both important risk factors for cardiovascular disease, type 2 diabetes, and psychological problems and other health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Additionally, the lack of BMI increase can be explained by the short observation period of the cross-sectional studies. In a 5-year observational study of more than 2000 children, it was shown that changes in BMI (+2.5 kg/m 2 ) can only be observed over a longer period of time (here, 5 years), even with physical inactivity [40].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the lack of BMI increase can be explained by the short observation period of the cross-sectional studies. In a 5-year observational study of more than 2000 children, it was shown that changes in BMI (+2.5 kg/m 2 ) can only be observed over a longer period of time (here, 5 years), even with physical inactivity [40].…”
Section: Discussionmentioning
confidence: 97%
“…A general lack of awareness, DCD's variability in presentation and comorbidity are the main reasons why identification is often delayed (Kennedy-Behr, Wilson, Rodger, & Mickan, 2013;Kirby, Davies, & Bryant, 2005;Wilson, Ruddock, Smits-Engelsman, Polatajko, & Blank, 2013), or even ignored. However, early identification is recommended to avoid commonly occurring secondary problems, such as social and emotional difficulties (Kirby, Sugden, & Purcell, 2014;Rigoli, Piek, Kane, & Oosterlaan, 2012;Wagner, Bös, Jascenoka, Jekauc, & Petermann, 2012;Viholainen, Aro, Purtsi, Tolvanen, & Cantell, 2014), health problems and inactivity (Hendrix, Prins, & Dekkers, 2014;Joshi et al, 2015;Rivilis et al, 2011), or academic problems (Cantell, Smyth, & Ahonen, 2003;Kantomaa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed discussion of the fitness results, please see King-Dowling et al 12. Given that these differences have been consistently observed among older children with DCD,10 18 39–41 it is likely that the differences in body composition will become more pronounced and physical activity will begin to appear as children age.…”
Section: Cohort Descriptionmentioning
confidence: 99%